Density Functional Theory Investigations of D-A-D' Structural Molecules as Donor Materials in Organic Solar Cell - Chen, Junxian; Liu, Qingyu; Li, Hao; Zhao, Zhigang; Lu, Zhiyun; Huang, Yan; Xu, Dingguo (Frontiers in Chemistry, 2018)
Squaraine core based small molecules in bulk heterojunction organic solar cells have received extensive attentions due to their distinguished photochemical properties in far red and infrared domain. In this paper, combining theoretical simulations and experimental syntheses and characterizations, three major factors (fill factor, short circuit and open-cirvuit voltage) have been carried out together to achieve improvement of power conversion efficiencies of solar cells. As model material systems with D-A-D' framework, two asymmetric squaraines (CNSQ and CCSQ-Tol) as donor materials in bulk heterojunction organic solar cell were synthesized and characterized. Intensive density functional theory computations were applied to identify some direct connections between three factors and corresponding molecular structural properties. It then helps us to predict one new molecule of CCSQ'-Ox that matches all the requirements to improve the power conversion efficiency.